Adsorption Behavior of Water on Virgin and Modified Cyclodextrin - Fumihiko Ogata (2020)
2020 The Pharmaceutical Society of Japan Relationship between water molecules and parent and hydroxypropylated cyclodextrins (denoted as CD and HP-CD) was assessed in this paper. The trends in ad-desorption isotherms of CD for water molecule were quite diŠerent compared to those of HP-CD. Ad-desorption isotherms of CD showed the hysteresis under our experimental conditions. The molar ratio of hydration (R-value) using a-CD, b-CD, g-CD, HP-a-CD, HP-b-CD, and HP-g-CD was 7.1, 11.4, 13.5, 12.5, 14.0, and 16.7, respectively. These results indicated that the adsorption capability of water molecule of HP-CD was greater than that of CD. Additionally, the changes in characteristics of CD and HP-CD at diŠerent water activity conditions were demonstrated. X-ray diŠraction patterns were signicantly diŠerent between CD and HP-CD. The crystal structure of HP-a-CD, HP-b-CD, and HP-g-CD showed amorphous at diŠerent water activity conditions. Finally, sorption entropy and heat of sorption of water molecules were calculated in this experiment. In summary, these results provide useful information for understanding the relationship between water molecules and parent and hydroxypropylated cyclodextrins.